Phenotypic Similarities and Differences of Genetic Characteristic Boer and PE Goat Yield Crossbreeding 1st and 2nd Generation - Rosidi Azis; Gatot Ciptadi; S. Suyadi (Chalaza Journal of Animal Husbandry, 2020)
This research aimed to analyze the phenotypic similarity and genetic characteristics of 1st and 2nd generation (G1 and G2) goat of Boer and PE goat yield crossbreeding. The number of offsprings of G1 and G2 was46 and 28 goats, respectively. Data analysis of phenotypic characteristics was estimated by calculating the opportunities of the number of the appearance of G1 and G2 offspring. The result showed that the percentages of the G2 of  W11 similarity (67.86%) more significant than G1 (26.09%).  The W21was the G1 (45.65%) higher than G2 (10.71%), and W31 was G1 (28.26%) higher than G2 (21.43%). It concluded that G2 had phenotypic similarities of the characteristic (color) in total progeny. The G2 goat displays the phenotypic characters of inheritance (color)patterns that had more significant similarity than the results of the G1, as well as similarities in morphological characters that were different from the G1. The characteristics (colors) in the G2 had dark brown head color greater than G1, and body conformation approaches to Boer goat. Other colors like light brown, plain white, black, and straight black on G1 greater than G2.